THE EFFECTIVENESS OF ANIMATION VIDEO IN VOCABULARY LEARNING FOR ENGINEERING STUDENTS ELEVETH GRADE OF VOCATIONAL SCHOOL - Ashidiqi, Nazam Ashidiqi Imaduddin; Moh. Arifin (FKIP, Universitas Billfath Lamongan, 2025)
Abstrak: This research aims to investigate the effectiveness of animation video in improving students’ vocabulary achievement and to explore students’ responses toward the use of multimedia in vocabulary learning. The research employed a quasi-experimental design involving two eleventh-grade classes from a vocational school: the experimental class (TKJ), which was taught using animation videos, and the control class (TKR), which received conventional instruction. Richard Mayer’s Multimedia Learning Theory served as the theoretical foundation, emphasizing the cognitive benefits of combining verbal and visual elements. Data were collected through pre-tests, post-tests, and classroom observations. The results of the Mann-Whitney U Test revealed a significance value of 0.000 < 0.05, indicating a statistically significant difference between the two groups. Students in the experimental group scored higher and showed more positive responses toward the learning process. The Students were more motivated, engaged, and found vocabulary easier to understand through animation. In conclusion, the use of animation video not only improves vocabulary achievement significantly but also fosters a more interactive and engaging learning environment for vocational school students. Abstract: Penelitian ini bertujuan untuk menyelidiki efektivitas video animasi dalam meningkatkan pencapaian kosakata siswa dan untuk mengeksplorasi tanggapan siswa terhadap penggunaan multimedia dalam pembelajaran kosakata. Penelitian ini menggunakan desain kuasi-eksperimental yang melibatkan dua kelas kelas sebelas dari sebuah sekolah kejuruan: kelas eksperimen (TKJ), yang diajar dengan menggunakan video animasi, dan kelas kontrol (TKR), yang menerima instruksi konvensional. Teori Pembelajaran Multimedia dari Richard Mayer menjadi landasan teori, yang menekankan pada manfaat kognitif dari penggabungan elemen verbal dan visual. Data dikumpulkan melalui pre-test, post-test, dan observasi kelas. Hasil dari Mann-Whitney U Test menunjukkan nilai signifikansi sebesar 0,000 < 0,05, yang menunjukkan perbedaan yang signifikan secara statistik antara kedua kelompok. Siswa dalam kelompok eksperimen mendapatkan nilai yang lebih tinggi dan menunjukkan respon yang lebih positif terhadap proses pembelajaran. Siswa lebih termotivasi, terlibat, dan menemukan kosakata yang lebih mudah dipahami melalui animasi. Kesimpulannya, penggunaan video animasi tidak hanya meningkatkan pencapaian kosakata secara signifikan, tetapi juga menumbuhkan lingkungan belajar yang lebih interaktif dan menarik bagi siswa sekolah kejuruan.